2005
DOI: 10.1097/01.ede.0000164813.46859.63
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Leukemia and Socioeconomic Status in Canada

Abstract: This analysis suggests that high SES is a true risk factor for childhood leukemia and that inconsistent results from other studies may be related to differences in case ascertainment or study participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 20 publications
5
75
2
1
Order By: Relevance
“…The proportion of county families living below the poverty level was inversely associated with incidence of ALL among females. Studies of SES and childhood ALL have been inconsistent, with elevated rates in higher-SES areas found by some (Pinkel and Nefzger, 1959;Fasal et al, 1971;Sanders et al, 1981;McWhirter, 1982;Laval et al, 1988;Cook-Mozaffari et al, 1989;Alexander et al, 1990a;Kinlen et al, 1995;Stiller and Boyle, 1996;Dockerty et al, 2001;Borugian et al, 2005), but not others (Alexander et al, 1990b;Kinlen et al, 1993;Dickinson and Parker, 1999). Our findings for household income and proportion of households below the poverty level better fit the former group, though from the shape of the curves, it appears that the issue is abject poverty rather the continuum of SES per se.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The proportion of county families living below the poverty level was inversely associated with incidence of ALL among females. Studies of SES and childhood ALL have been inconsistent, with elevated rates in higher-SES areas found by some (Pinkel and Nefzger, 1959;Fasal et al, 1971;Sanders et al, 1981;McWhirter, 1982;Laval et al, 1988;Cook-Mozaffari et al, 1989;Alexander et al, 1990a;Kinlen et al, 1995;Stiller and Boyle, 1996;Dockerty et al, 2001;Borugian et al, 2005), but not others (Alexander et al, 1990b;Kinlen et al, 1993;Dickinson and Parker, 1999). Our findings for household income and proportion of households below the poverty level better fit the former group, though from the shape of the curves, it appears that the issue is abject poverty rather the continuum of SES per se.…”
Section: Discussioncontrasting
confidence: 46%
“…Some studies reported elevated childhood leukaemia rates in higher-SES areas (Kinlen et al, 1995;Stiller and Boyle, 1996;Borugian et al, 2005), whereas other studies have found no association (Alexander et al, 1990b;Kinlen et al, 1993;Dickinson and Parker, 1999). This study aimed (1) to expand our understanding of the possible infectious nature of childhood ALL by examining its association with residential relocation, population change, and urbanisation, (2) to examine its relation with housing age (newlyconstructed housing may reflect population growth or influx, but has not been previously studied), and (3) to clarify its relationship with SES by examining household income and the proportion of families below the poverty level.…”
mentioning
confidence: 99%
“…Two suggested a relative protection of children living in the most deprived area (34,38) , one suggested an increased risk in this group (for residence at birth only (39) ) and one showed no effect (37) . However, overall, the effect sizes were small and only evident in the most extreme quantiles (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown an elevated risk of childhood leukaemia or ALL in areas of higher socioeconomic status (Githens et al, 1965;Alexander et al, 1990a;Draper et al, 1991;Stiller and Boyle, 1996;Borugian et al, 2005). In our 1979 -1985 study, it was suggested that the socioeconomic gradient might be largely due to population mixing (Stiller and Boyle, 1996), but the present study showed a substantial effect of socioeconomic status after urbanisation and incomers' diversity had been allowed for (see above).…”
Section: Discussionmentioning
confidence: 99%